EFFICIENCY OF PHARMACY MANAGEMENT IN MANAGING EXPIRED DRUGS, DAMAGED DRUGS, AND UNUSED DRUGS - Gemy Nastity Handayany; Fathul (Homes Journal = Hospital Management Studies Journal, 2025)
Backround: One of the services provided by pharmaceutical activities is drug management which begins with selection, planning, procurement, receipt, storage, distribution, control, destruction, and administration. In addition to maintaining service quality standards, the goal is to ensure the continued availability and affordability of pharmaceutical preparations and health supplies that are reasonable, effective, and efficient. Objective: The purpose of this study was to assess the extent to which drug management in hospitals affects the condition of drugs that are no longer usable, damaged or unused. Methods: The design of this study was descriptive retrospective with data obtained through observation and interviews and analyzed statistically using the chi square test on the latest version of SPSS software. The study population included all drugs available in the hospital during 2024, with samples in the form of damaged expired drugs and unused drugs. Result: The results of the study showed that the percentage of expired drugs reached 0.093103%, damaged drugs were 0.02069% and unused drugs were 0.006897%, with the total financial losses incurred quite significantly for the hospital. The results of the chi square test showed a significant relationship between drug management and the incidence of expired, damaged and unused drugs (p value = 0.028) based on interviews with pharmacy staff it was found that the main causes of this problem include changes in prescribing patterns, BPJS restrictions that reduce stock movement, and lack of control of drug rotation in the pharmacy warehouse. Conclusion: This study concludes that the management of drug management at Haji Hospital In Makassar needs to be improved, especially in planning and monitoring inventory to reduce the number of expired, damaged and unused drugs. Implementation of a better rotation system and adaptation of prescription policies according to patient needs are expected to minimize future losses.